Weighing the importance of surface forcing on sea ice: a September 2007 modelling study. (29th March 2014) - Hunke, E. C.
Abstract: The sea ice minimum of September 2007 is represented in a 50‐year simulation using the Los Alamos Sea Ice Model, CICE, in spite of the fact that only four atmospheric forcing fields vary interannually in the model simulation; all other atmospheric and oceanic forcing data are monthly mean climatologies. Simulation results support prior conclusions that an anomalous pressure pattern, ice‐ocean albedo feedback effects on sea surface temperature, and the long‐term sea ice thinning trend are primarily responsible for the sea ice minimum of 2007. In addition, the simulation indicates that cloudiness, precipitation, and other forcing quantities were of secondary importance. Here we explore the importance of applied atmospheric and oceanic surface forcing for the 2007 sea ice minimum event, along with a group of model parameterizations that control the surface radiation budget in sea ice (melt ponds). Of the oceanic forcing fields acting on sea ice, only the sea surface temperature varied interannually for simulating the 2007 event. Interannual variations of temperature and humidity play a role in the radiation balance applied at the snow and ice surface, and they both have the potential to significantly affect the ice edge. However, humidity (exclusive of clouds) is far less influential on ice volume than is air temperature. The inclusion of albedo changes due to melt ponding is also crucial for determining the radiation forcing experienced by the ice. We compare the effects of four different pond parameterizations now available in CICE for the September 2007 case, and find that while details may differ, they all are able to represent the 2007 event. The impact of feedbacks associated with the radiation balance differs among the pond simulations, presenting a key topic for future study.